Flametti: oder vom Dandysmus der Armen - Ball, Hugo, 1886-1927 (Salt Lake City, UT : Project Gutenberg, 2001)
"Flametti: oder vom Dandysmus der Armen" by Hugo Ball is a novel written during the early 20th century. The story revolves around Flametti, a character deeply embedded in the world of a variety ensemble, navigating his struggles and interactions with fellow artists and the complexities of a precarious artistic life. At the start of the novel, we are introduced to Flametti as he wakes up in his modest apartment, prepares for the day, and checks on the finances of his variety troupe. His interactions with a series of eccentric characters, including his grouchy housekeeper Theres and various members of his ensemble, paint a vivid picture of his chaotic yet vibrant life. Flametti's determination to manage his artistic endeavors despite financial uncertainty and the burdens of running his troupe reflect the struggles of artists seeking recognition and stability in their careers. As he heads out to fish and engages with the local community, the mood is characterized by a blend of humor, melancholy, and a quest for artistic vitality. The opening sets the stage for a narrative rich in character dynamics and the exploration of the performative life. (This is an automatically generated summary.)
Release date is 2001-10-01
This etext was prepared by Michael Pullen
Keywords: Switzerland -- Fiction